2012
DOI: 10.1111/j.1743-6109.2012.02743.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Evoked Vasodilation is Blunted in Penile Arteries from Zucker Diabetic Fatty Rats

Abstract: Introduction Endothelium-derived relaxing factors such as nitric oxide (NO), prostanoids, and endothelium-derived hyperpolarizing factor (EDHF) are thought to play an important role in vasodilation of penile arteries. Aim The present study investigated the mechanisms involved in flow- and acetylcholine-induced vasodilation in penile arteries, and whether acetylcholine- and flow-mediated vasodilation is altered in Zucker diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 55 publications
2
17
1
Order By: Relevance
“…In addition to NO, an EDH, a non‐NO non‐prostanoid component, also plays a role in the acetylcholine‐evoked relaxation in the present study. These results are in agreement with previous observations where the presence of both NO and EDH in acetylcholine‐evoked relaxation have been demonstrated in penile resistance arteries isolated from human beings , rat , horse and rabbit .…”
Section: Discussionsupporting
confidence: 94%
“…In addition to NO, an EDH, a non‐NO non‐prostanoid component, also plays a role in the acetylcholine‐evoked relaxation in the present study. These results are in agreement with previous observations where the presence of both NO and EDH in acetylcholine‐evoked relaxation have been demonstrated in penile resistance arteries isolated from human beings , rat , horse and rabbit .…”
Section: Discussionsupporting
confidence: 94%
“…Mean arterial blood pressure (MAP) and intracavernous blood pressure (ICP) was measured using catheters placed, respectively, in the carotid artery and corpus cavernosum as previously described 11 . Maximal stimulation (6 V, 1ms, 16 Hz, 60 s) was applied to check maximal erectile function at the beginning of each experiment, before incremental frequencies (2, 4, 8 and 16 Hz) were applied at 1.5, 3, and 6 V. At the end of the experiment the maximal response was repeated to ensure that the cavernous nerve was intact and erectile function maintained.…”
Section: Methodsmentioning
confidence: 99%
“…In rat penile arteries, we found that K Ca 2.3 and K Ca 3.1 channels contribute to flow-induced vasodilation and that these dilatations were impaired in type 2 diabetic Zucker diabetic fatty (ZDF) rats 11 . Moreover, in mesenteric arteries from ZDF rats an opener of K Ca 2.1–3 and K Ca 3.1 channels restored endothelium-derived hyperpolarization (EDH) type relaxations induced by acetylcholine 12 .…”
Section: Introductionmentioning
confidence: 95%
“…Like ageing, diabetes impacts vascular function. In fact, the impairment of endothelium-dependent vasodilatation is a frequent finding in arteries from diabetic animals and patients in both in vivo and ex vivo settings Angulo et al 1998;Kim et al 2002;Rodríguez-Mañas et al 2003;Angulo et al 2003;Molnar et al 2005;Schjørring et al 2012). Furthermore, endothelial dysfunction is a predictor of CVD in diabetic patients (van Slotten et al 2014).…”
Section: Vascular Dysfunction In Diabetesmentioning
confidence: 99%
“…; Schjørring et al . ). Furthermore, endothelial dysfunction is a predictor of CVD in diabetic patients (van Slotten et al .…”
Section: Introductionmentioning
confidence: 97%